Arthritis and dentistry. Issue 1 (March 2022) - Bharmal, Rozana Valiji; Chia, Matthew
Arthritis is a common condition affecting millions of people in the UK and worldwide. All members of the dental team will be seeing and treating patients with this condition, and it is important to understand the disease, its management and medications used. This article outlines the five most common types of arthritis: osteoarthritis (OA), rheumatoid arthritis (RA), axial spondyloarthritis (sPA), juvenile idiopathic arthritis (JIA), and gout. It further discusses the medications used to treat these conditions and any dental implications. Finally, advice is offered on considerations for the dental team when treating such patients.